2016
DOI: 10.2174/1874205x01610010083
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Senescence in Cultured RPE Cells

Abstract: The aim of this research is to determine whether oxidative stress induces cellular senescence in human retinal pigment epithelial cells. Cultured ARPE19 cells were subjected to different concentrations of hydrogen peroxide to induce oxidative stress. Cells were seeded into 24-well plates with hydrogen peroxide added to cell medium and incubated at 37°C + 5% CO2 for a 90-minute period at 0, 300, 400 and 800 micromolar (MCM) hydrogen peroxide. The number of viable ARPE19 cells were recorded using the Trypan Blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Senescent cells secret numerous kinds of pro-inflammatory cytokines, chemokines, growth factors and proteases, exemplifying what is referred to as a senescence-associated secretory phenotype (SASP) [ 23 ]. Further, oxidative stress also plays an important role in RPE senescence [ 24 26 ]. Congruent with this, we treated additional ARPE-19 cells with 10 µM FK866 for 72 h, the dose and time-point most effective at reducing NAD + and promoting cellular senescence without robust toxicity, and monitored them for expression of the pro-inflammatory cytokines IL-6 and IL-8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Senescent cells secret numerous kinds of pro-inflammatory cytokines, chemokines, growth factors and proteases, exemplifying what is referred to as a senescence-associated secretory phenotype (SASP) [ 23 ]. Further, oxidative stress also plays an important role in RPE senescence [ 24 26 ]. Congruent with this, we treated additional ARPE-19 cells with 10 µM FK866 for 72 h, the dose and time-point most effective at reducing NAD + and promoting cellular senescence without robust toxicity, and monitored them for expression of the pro-inflammatory cytokines IL-6 and IL-8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, if the majority of RPE cells are senescent, the compensating mechanisms can fail and lead to AMD progression. Oxidative stress has been shown to induce senescence in the RPE cells, but the exact mechanism has not been clarified (Aryan et al, 2016). The release of pro-inflammatory cytokines and ROS by senescent cells, DNA damage-induced senescence, induction of senescence in neighboring cells, as well as the interplay between senescence and autophagy are considered to regulate RPE degeneration (Sikora et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we wished to test the effects of CS on cellular senescence. Senescence of RPE cells has been identified in many studies as a key mechanism in AMD pathogenesis [ 43 , 44 ], and has been shown to be induced by oxidative stress [ 45 , 46 ]. In our study, we found that CS induces senescence in ARPE-19 cells, as seen by an increase in SA-β-galactosidase positive cells ( Fig 7A and 7B ), a result that has been studied before [ 9 ].…”
Section: Discussionmentioning
confidence: 99%